2023
DOI: 10.3233/jpd-225122
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Relevance of Digital Measures to Meaningful Symptoms and Impacts in Early Parkinson’s Disease

Jennifer R. Mammen,
Rebecca M. Speck,
Glenn M. Stebbins
et al.

Abstract: Background: Adoption of new digital measures for clinical trials and practice has been hindered by lack of actionable qualitative data demonstrating relevance of these metrics to people with Parkinson’s disease. Objective: This study evaluated of relevance of WATCH-PD digital measures to meaningful symptoms and impacts of early Parkinson’s disease from the patient perspective. Methods: Participants with early Parkinson’s disease (N = 40) completed surveys and 1:1 online-interviews. Interviews combined: 1) symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…We did not assess patients off medication or compare naive patients to those on medications or assess treatment effects. These and other important questions should be addressed in ongoing 42,45,50 and future studies. Nonetheless, this is one of the largest studies investigating digital mobility technology in PD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We did not assess patients off medication or compare naive patients to those on medications or assess treatment effects. These and other important questions should be addressed in ongoing 42,45,50 and future studies. Nonetheless, this is one of the largest studies investigating digital mobility technology in PD.…”
Section: Discussionmentioning
confidence: 97%
“…In recent work, patients with PD shared their perspective that slowness of movement was among their most bothersome and important symptoms 40 . Patients reported that PD symptoms had the greatest impact on sleep, job functioning, exercise, communication, relationships, and sense of being, 41 aspects of daily living that can be partially reflected in real‐world function collected via digital measures 42 . Indeed our findings show that the measures most strongly associated with disease severity were not related to quality but rather to function coming from domains of sleep (NB) and activity quantity and distribution.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Supplement B, interview questions focused on understanding PD symptoms, experiences, characteristics and impacts of symptoms, and relative bothersomeness. Symptom mapping [20] was used to delineate all personal symptoms and impacts as shown in Fig. 2.…”
Section: Online Interviewmentioning
confidence: 99%
“…2. Symptom mapping is a hybrid mixed-method technique that enables the collection of qualitative data in a quantifiable manner by active categorization of experiences inside of a structured framework [20]. Interviews were conducted by a qualitative researcher experienced in these methods (JM; white, female, PhD-prepared advanced practice nurse, unacquainted with participants).…”
Section: Online Interviewmentioning
confidence: 99%
See 1 more Smart Citation